Analisis Biaya dan Pendapatan Usaha Kelapa Muda di Kota Kendari - Samsul, Samsul; Rosmawaty, Rosmawaty; Indarsyih, Yusna (Department of Agribusiness, Halu Oleo University, 2018)
This study aims to recognize (1) the cost incurred in the marketing of young coconut in Kendari City, (2) income earned on young coconut marketing business in Kendari City and (3) R/C cost efficiency at young coconut marketing business in Kota Kendari. This study uses Qualitative method. The population of this research is all sellers of young coconuts in Kendari City.Â Determination of sample in this research is using census method. The results of this study show that (1) the average cost incurred in the marketing of young coconut is Rp 6,831,584/month, (2) while the total cost of revenue is Rp 59,547,827 per month with the average value of Rp 4.253.416 per month and (3) cost efficiency R/C ratio on marketing of young coconut is 1.6 means greater than 1 in the sense that young coconut marketing business is profitable and feasible to Developed.